A terapia ocupacional como campo de conhecimento científico no Brasil: formação pós-graduada e atuação profissional de seus mestres e doutores - Folha, Otavio Augusto de Araujo Costa (Universidade Federal de São Carlos, 2019)
Scientific Institutionalization is a current challenge of occupational therapy in Brazil as it celebrates 50 years of its professional regulation. In recent years, there has been an intense movement of Brazilian occupational therapists in the development of strategies to address this challenge. One of these strategies involves monitoring the training and participation of its researchers in the development of research and graduate activities. In this study, the thesis is presented that talking about the involvement of occupational therapists in research does not mean affirming the occurrence of research in occupational therapy. This finding was developed from the characterization of postgraduate education and professional practice of occupational therapists with masters and doctorates in Brazil. This is a descriptive and correlational study, based on documents, with a descriptive and analytical quantitative approach. We analyzed the Lattes Curricula of occupational therapists registered in CNPq Lattes Platform trained and / or working in Brazil. Information was also collected about undergraduate and postgraduate occupational therapists in the Capes Dissertation and Thesis Catalog, the Sucupira Platform and the E-mec Platform. Among the results, it was identified that by the end of 2017, there were 859 masters and 329 doctors in the country. The scientific field of Brazilian occupational therapy consists predominantly of women (93%). It has a late and time-consuming process of constitution, with 62.61% of its masters and doctors graduated from 2010. Their researchers were trained in 237 master's programs and 27 doctoral programs, with the predominance of master's training in 11 areas. Assessment (83%) and PhD in 10 areas (84%). There has been a change in the profile of postgraduate education, influenced by regional diversity and the participation of occupational therapists as mentors in master and doctoral courses. There is considerable regional asymmetry in the distribution of masters and doctors in the Brazilian regions, where 55.47% of postgraduates are located in the Southeast. Only 52% of masters and doctors participate in any research group, and of these, only 59% research occupational therapy. There has been a significant increase in the training of new researchers in undergraduate research and postgraduate studies. More than 90% of the bibliographic production of occupational therapists with master's and doctorate degrees occurred from the 2000s. However, 7 out of 10 articles produced by these professionals do not mention the descriptor “occupational therapy” in its title, abstract and / or words. -key. In this way, several associations were observed between postgraduate education and professional practice that imply the production of scientific knowledge developed by these professionals. The implications of these data for the scientific institutionalization of occupational therapy in Brazil are discussed.
Occupational therapy as a field of scientific knowledge in Brazil: Graduate education and professional practice of its masters and doctors
La terapia ocupacional como campo de conocimiento científico en Brasil: educación de posgrado y desempeño profesional de sus maestros y doctores
Keywords: Terapia ocupacional; Educação de Pós-Graduação; Educação Superior; Institucionalização científica; Pesquisa; Brasil; Occupational therapy; Scientific Institutionalization; Higher Education; Educación de Posgrado; Educación Superior; Institucionalización científica; CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL